The Role and Function of Islamic Counseling in Fostering Student Morals - Asriana Asriana; Saiful Akhyar Lubis; Nurmawati Nurmawati (Newinera Publisher, 2026)
This study examines the role and function of Islamic counseling in fostering students’ moral character across state Islamic senior high schools (MAN) in Padangsidimpuan. Using a qualitative multisite design, the research investigates how Islamic counseling practices integrated with the roles of PAI (Islamic Education) teachers contribute to strengthening students’ religious values and behavioral discipline. Data were obtained through in-depth interviews, observations, and documentation across two MAN institutions, revealing that counseling interventions grounded in Qur’anic principles, prophetic character, and spiritual development effectively address contemporary moral challenges faced by adolescents in the digital era. The findings highlight that collaboration between BK (Guidance and Counseling) teachers and PAI teachers plays a crucial role in creating a supportive environment for moral cultivation, particularly in mitigating issues such as declining discipline, digital addiction, and weakening religious awareness. The study concludes that Islamic counseling provides a holistic framework for character formation, integrating cognitive, affective, and behavioral domains. Strengthening professional competence among counselors and enhancing school-based religious programs are recommended to ensure sustainable character development in madrasah settings.